PENGARUH PENGGUNAAAN MEDIA PEMBELAJARAN BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR SISWA KELAS II PADA MATA PELAJARAN BAHASA INDONESIA SDN 08 TIUMANG - Feby kharisna; Futri Afriyani; Sri Yunimar Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
To create a conducive learning atmosphere and achieve optimal results, an educator needs to have the awareness and ability to innovate in the world of education. One form of innovation is by utilizing learning media that are effective, interesting, fun, and provide meaning for students. In this context, Wordwall learning media was chosen as a means of supporting learning. This research aims to find out how the use of wordwall-assisted learning media affects the learning outcomes of class II students in Indonesian language subjects at SDN 08 Tiumang This research method uses pre-experiment, with a one group pre-test post-test design. The research subjects were all class II students at SDN 08 Tiumang with a total of 7 people. The sampling technique in this research was saturated sampling with a sample size of 7 people. Data collection techniques in the form of pretest and posttest using test questions in the form of 16 multiple choice questions. The data analysis technique in this research uses the normality test and paired samples t-test. The results of the paired samples t-test show a significance level of 0.000<0.05, which means Ha is accepted and Ho is rejected. So it was concluded that the use of wordwall-assisted learning media had an effect on the learning outcomes of class II students in the Indonesian language subject at SDN 08 Tiumang